Modified unsteady vortex-lattice method to study flapping wings in hover flight - Roccia, Bruno Antonio (2013)
A numerical-simulation tool is developed that is well suited for modeling the unsteady nonlinear aerodynamics of flying insects and small birds as well as biologically inspired flapping-wing micro air vehicles. The present numerical model is an extension of the widely used three-dimensional general unsteady vortex-lattice model and provides an attractive compromise between computational cost and fidelity. Moreover, it is ideally suited to be combined with computational structural dynamics to provide aeroelastic analyses. The present numerical results for a twisting, flapping wing with neither leading-edge nor wing-tip separations are in close agreement with the results obtained in previous studies with the Euler equations and a vortex-lattice method. The present results for unsteady lift, mean lift, and frequency content of the force are in good agreement with experimental data for the robofly apparatus. The actual wing motion of a hovering Drosophila is used to compute the flowfield and predict the lift force. The downward motion of the fluid particles revealed in the graphics of the calculated wake indicates the presence of lift. Moreover, the calculated mean lift is in close agreement with the weight of a Drosophila. The results presented in this paper definitely show that the interaction between vortices is the main feature that allows insects to generate enough lift to stay aloft. The present results warrant the use of this general version of the unsteady vortex-lattice method for future studies.